A grassroots research approach for branding urban districts. (12th June 2019) - Pasalar, Celen; Hallowell, George Dewey
Abstract : Purpose: To produce effective urban district branding strategies, the factors impacting its unique characteristics and identity must be examined first. The purpose of this paper is to present a bottom-up participatory process for uncovering the identity of an urban district to ensure that its community goals and future branding are consistent and genuine. Design/methodology/approach: This paper examines a recently completed grassroots effort that was used to uncover key physical, economic and cultural resources of the Southwest Raleigh district. Interdisciplinary methods, including surveys, interviews, mapping and economic analysis, were used to reveal how residents and businesses perceived the district's identity. Findings: The study revealed strong connections between a growing economy and factors related to liveability and identity, such as walkability, proximity, connectivity and availability of amenities. It provided a framework for communities to understand the forces of change that may influence the urban identity and potential branding strategies that would align with growing creative district goals. Practical implications: Analyzing and evaluating the factors involved in the district's identity, including diversified economies, demographics and urban qualities, is essential to the creation of an authentic brand that aligns with community perceptions. Social implications: A research strategy is necessary to uncover the identity of a growing city. This requires a thorough assessment of its unique, localized characteristics, including the perceptions of its residents and businesses. Originality/value: This paper and its outcomes can inform future in-depth investigations using similar comprehensive and bottom-up approaches for uncovering perceptions and urban identity in support of growing creative economies.